Understanding the history of the late Roman synagogue at Huqoq in Israel’s Galilee through radiocarbon dating and observations on site formation - Dennis Mizzi; Daniel Schindler; Elisabetta Boaretto; Michael Chazan; Jodi Magness (PLoS ONE, 2025)
Galilean-type synagogues are monumental, basilical structures found in northern Israel that have long been dated, mainly on stylistic grounds, to the 2nd – 3rd centuries CE. This chronology is influenced by historical considerations – specifically, the notion that monumental synagogues must have been constructed before Jews came under Christian rule in the early 4th century. However, the stratigraphic contexts of the pottery and coins associated with the foundation of these buildings suggest they represent an architectural innovation dating to the 4th (especially the later 4th) to 6th centuries CE. The Huqoq Excavation Project was initiated in 2011 with the goal of determining the construction date of a Galilean-type synagogue through controlled stratigraphic excavation, including the systematic collection of samples for radiocarbon dating along with micromorphological analysis of the fill deposits. Here we present the initial results of these analyses, which indicate that the radiocarbon ages conform with the pottery data to place the construction of the Huqoq synagogue in the late 4th – early 5th centuries (late Roman period). However, the ages of dated samples from thick fills overlying the floor, which were deposited when the synagogue was rebuilt and expanded in the early 14th century (late medieval/Mamluk period) do not reflect the stratigraphic sequence.